2012
DOI: 10.1128/jcm.00796-12
|View full text |Cite
|
Sign up to set email alerts
|

The Genus Corynebacterium and Other Medically Relevant Coryneform-Like Bacteria

Abstract: Catalase-positive Gram-positive bacilli, commonly called “diphtheroids” or “coryneform” bacteria were historically nearly always dismissed as contaminants when recovered from patients, but increasingly have been implicated as the cause of significant infections. These taxa have been underreported, and the taxa were taxonomically confusing. The mechanisms of pathogenesis, especially for newly described taxa, were rarely studied. Antibiotic susceptibility data were relatively scant. In this minireview, clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
287
0
24

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(317 citation statements)
references
References 47 publications
6
287
0
24
Order By: Relevance
“…Many reports have mentioned that it remains a priority to identify Corynebacterium spp. at the species level in clinics (1,19,23). According to our results, we agree with the previously proposed opinion that partial rpoB sequencing is a simple and efficient method for the identification of Corynebacteria (23).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Many reports have mentioned that it remains a priority to identify Corynebacterium spp. at the species level in clinics (1,19,23). According to our results, we agree with the previously proposed opinion that partial rpoB sequencing is a simple and efficient method for the identification of Corynebacteria (23).…”
Section: Discussionsupporting
confidence: 81%
“…consists of Gram-positive rods with 88 valid, published species, including 3 species in press or published since the Bergey's Manual chapter was compiled (1). Corynebacterium spp.…”
Section: Introductionmentioning
confidence: 99%
“…C. striatum and C. amycolatum are part of the normal human skin flora, and although increasingly recognized as potential pathogens in hospitalized and immunocompromised patient populations such as those suffering from endocarditis, bloodstream and catheter infections, empyema, and pneumonia [5], there are no reports in the literature of GI infections caused by these organisms. Although little is known about these organisms in the gut, a Danish study of upper jejunal fluid from 51 children with no known GI disease reported that Corynebacterium sp.…”
Section: Commentmentioning
confidence: 99%
“…Many strains of the genus (about 70 %) have been isolated from clinical materials or from other animalrelated materials. Some species of the genus are medically relevant and can cause infections, while some have industrial uses (Bernard & Funke, 2012;Bernard, 2012). During investigations into cultivable actinomycetes from animal faeces, strain YIM 101505 T was isolated from the faeces of a healthy primate, Assamese macaque,and its taxonomic position was studied.…”
mentioning
confidence: 99%
“…Similarities with other species of this genus were below 97 % based on the 16S rRNA gene. (Bernard & Funke, 2012;Bernard, 2012). During investigations into cultivable actinomycetes from animal faeces, strain YIM 101505 T was isolated from the faeces of a healthy primate, Assamese macaque,and its taxonomic position was studied.…”
mentioning
confidence: 99%